Coping with the death of a child : an integrated clinical approach to working with bereaved families - Schiffman, Darin D. (New York : Routledge, 2019)
Coping with the Death of a Child shows clinicians how to integrate various therapeutic modalities and clinical approaches to grief therapy into one comprehensive model linked to positive change. This integrated model shows mental health professionals how to offer practical and emotional support to the bereaved using descriptions of treatments, care protocols, and guidelines. Through this approach, practitioners can foster interpersonal support and growth among families, even when grieving styles and timing differ between individuals. Clinicians and the families they treat will come away from the book with tools for recognizing distorted and pathogenic exchanges between family members, for valuing the emotional elements of their individual experiences, and for shifting toward solution-focused activities.
Structuring interventions -- Perspectives of loss -- Trauma and grief -- Theories of grief and loss -- The bereaved family -- Relationships within the family -- Family systems and communication -- General approaches to treating the bereaved -- Forming the therapeutic alliance -- Encountering and assessing grief -- Toward a workable model -- Conclusions -- Appendices -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Children -- Death -- Psychological aspects; Loss (Psychology); Bereavement -- Psychological aspects; FAMILY & RELATIONSHIPS / Life Stages / General; PSYCHOLOGY / Developmental / General; PSYCHOLOGY / Developmental / Lifespan Development; PSYCHOLOGY / General; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family